Peran Program TPQ Sebelum Pembelajaran dalam Meningkatkan Kemampuan Membaca Al-Qur’an Anak Usia Dini - Riska Agustina; Faradia Eky Septiansa; Alifa Ghina Raudhatul Jannah; M.Bahri Musthofa (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The Qur'anic Learning Center Program (TPQ) is a form of non-formal Islamic education that plays an important role in developing Qur'an reading skills from an early age. Implementing TPQ activities before formal learning sessions is considered an effective strategy to build positive habits, improve discipline, and strengthen Qur'anic literacy among young children. This study aims to examine the role of TPQ programs conducted before classroom learning in improving Qur'an reading abilities among early childhood learners through a literature review approach. The method used is a library study by reviewing various books, scientific journals, and academic sources related to Islamic education, early childhood development, and Qur'an reading instruction. The findings indicate that TPQ activities conducted prior to formal learning provide several benefits, including improving recognition of Arabic letters, enhancing the accuracy of pronunciation according to proper articulation points, increasing fluency in Qur'an reading, and developing basic understanding of tajwid rules. Furthermore, the routine practice of reading the Qur'an before learning activities contributes to the development of religious character, improves learning concentration, and fosters a love for the Qur'an among children. A supportive learning environment and teaching methods that align with children's developmental stages are important factors in the success of TPQ programs. Based on the literature review, it can be concluded that TPQ programs conducted before classroom learning play a significant role in improving Qur'an reading skills among early childhood learners while strengthening Islamic values from an early age. Therefore, this program should continue to be developed and sustainably integrated into early childhood education activities.